-2x + 6y=4 5x + y = 6 using cramers rule

Question

-2x + 6y=4
5x + y = 6 using cramers rule

in progress 0
Peyton 5 months 2021-12-30T20:54:00+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-12-30T20:55:27+00:00

    Answer:

    The answer to your question is x = 1   y = 1

    Step-by-step explanation:

    Data

          -2x + 6y = 4           Equation l

           5x + y = 6              Equation ll

    Process

    1.- Calculate Δ

    Δ  =    | -2   6 |

              | 5    1 |  = (-2 x 1) – (5 x 6)

                           = -2 – 30

                           = – 32

    2.- Calculate Δx

    Δx =  | 4   6 |

            | 6    1 |   = (4 x 1) – (6 x 6)

                          = 4 – 36

                          = -32

    3.- Calculate Δy

    Δy = |  -2  4 |

           |  5   6  |  = (-2 x 6) – (5 x 4)

                          = -12 -20

                          = -32

    4.- Find x and y

    x = Δx/Δ = -32/-32 = 1

    y = Δy/Δ = -32/-32 = 1

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )